2021
DOI: 10.15446/profile.v23n1.85931
|View full text |Cite
|
Sign up to set email alerts
|

Exploring EFL Teaching and Learning Processes in Two Undergraduate Mandatory Courses

Abstract: This multiple case study explored the influence of English teachers’ methodological practices over undergraduate students’ learning processes in two English as a foreign language mandatory courses for different majors, at Universidad de Pamplona (Colombia). Data were gathered through non-participant observations, field notes, stimulated recall interviews, and semistructured interviews. Findings revealed that teacher-centeredness, the grammar-translation and audiolingual methods dominated the lessons; textbook-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…However, not all teachers possess the capacity to inspire students. The controller role is evident during specific instances such as making announcements, clarifying concepts, or leading question-and-answer sessions, particularly in language learning contexts (Durán & García, 2021). Additionally, there is acknowledgment that certain situations, like taking attendance or providing instructions, necessitate a controller's role.…”
Section: Teacher As Controllermentioning
confidence: 99%
“…However, not all teachers possess the capacity to inspire students. The controller role is evident during specific instances such as making announcements, clarifying concepts, or leading question-and-answer sessions, particularly in language learning contexts (Durán & García, 2021). Additionally, there is acknowledgment that certain situations, like taking attendance or providing instructions, necessitate a controller's role.…”
Section: Teacher As Controllermentioning
confidence: 99%
“…Different universities use and practice different teaching methodologies in EFL that are practical and effective teaching approaches (Durán & García, 2021). As some studies deal with teaching methodologies and practices in the EFL field, including substantial teaching factors and error correction approaches.…”
Section: Teaching Methods and Practices In Efl Education At Internati...mentioning
confidence: 99%
“…As some studies deal with teaching methodologies and practices in the EFL field, including substantial teaching factors and error correction approaches. In Colombia, Durán & García (2021) have found that in some universities, English language teaching is dominated by some methodologies which are focused mainly on grammar instruction. Except for Universidad Del Valle, the EFL teaching methodology was based on cooperative learning and the communicative approach.…”
Section: Teaching Methods and Practices In Efl Education At Internati...mentioning
confidence: 99%
See 2 more Smart Citations